A Preliminary Historical Report on Embracing Online Education in Occupational Therapy - Janel Anne Belarmino; Angela Bahle-Lampe (Scholarworks @ WMU, 2019)
The relevance and popularity of online occupational therapy education have been increasingly recognized. This paper describes the historical development of online occupational therapy education. Findings revealed three shifts in occupational therapy education, namely shifts in perception, in mode of instruction, and in the roles of teachers and students. The inception of online education in occupational therapy was a product of technological advancement and the demand for improved access to occupational therapy online education. The early phase of occupational therapy online education was confronted with challenges related to hesitance in the development and implementation of online programs and to negative perceptions about online education. The development and implementation of online occupational therapy programs were greatly shaped by factors such as technological tools, methods of teaching delivery, and the dynamics of teaching and learning processes. The potential of online occupational therapy education remains vast, but experts caution that quality should not be compromised.